Pengaruh Citra Merek, Kualitas Produk, Harga, Promosi Dan Kepercayaan Merek Terhadap Minat Beli Smartphone Apple (Studi Kasus Mahasiswa Universitas Islam Malang) - Rafsanjani, Rafli; Arifin, Rois; Utama, Satria Putra (UNIVERSITAS ISLAM MALANG, 2024)
Abstract This research was conducted to determine and analyze the influence of brand image, product quality, price, promotion and brand trust simultaneously and partially on purchasing interest. The population in this study was an unknown number of students at the Islamic University of Malang. The approach method uses a non-probability sampling technique, namely purposive sampling, namely a sample collection technique based on certain criteria using a questionnaire distributed to 90 respondents and using the SPSS analysis tool. The research results show that brand image, product quality, price, promotion and brand trust simultaneously influence purchasing interest and partially brand image, product quality, promotion and brand trust influence purchasing interest but price does not influence purchasing interest. Keywords: Brand Image, Product Quality, Price, Promotion, Brand Trust, Purchase Interest